Idiopathic Immune Complex-Mediated Membranoproliferative Glomerulonephritis: A Significant Cause of End-Stage Kidney Disease in Children - M, Bouchoual; K, Dadi; A, El Khand; M, El Ouazzani; S, Anibar; M, Jabrane; M, Arrayhani (Journal of Clinical Nephrology, 2025)
Introduction: Membranoproliferative glomerulonephritis (MPGN) is a significant cause of glomerulopathy and chronic kidney disease (CKD) or end-stage renal disease (ESRD) in children. The deposition of circulating immune complexes in the glomerulus and abnormal activation of the alternative complement pathway is believed to trigger the disease. However, there is limited knowledge regarding the optimal treatment and prognosis for children with immune complex-associated MPGN (IC-MPGN) and C3 glomerulopathy (C3G). Case report: We report the case of a 14-year-old child admitted for rapidly progressive glomerulonephritis with anuria managed on haemodialysis. The kidney biopsy showed an appearance compatible with MPGN on light microscopy, with immunoglobulin and complement C3 deposits on direct immunofluorescence. The prognosis was poor, with rapid progression to ESRD despite treatment combining corticosteroid therapy and immunosuppressants. Discussion and conclusion: Evaluating the effectiveness of different therapeutic approaches for MPGN in children is challenging due to the small sample sizes and the short duration of the published controlled studies. As a result, it is crucial to conduct more comprehensive trials that focus on both prognosis and treatment options.